2012
DOI: 10.1590/s1517-86922012000500012
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do ultrassom terapêutico associados ao alongamento estático sobre parâmetros histomorfométricos longitudinais de sóleos imobilizados de ratos

Abstract: The muscle tissue is endowed with plasticity that adapts to different stimuli. Immobilization causes damage to the musculature including atrophy, loss of muscle strength and extensibility. The stretching and ultrasound treatment modalities are used to speed up muscle repair process as they can increase protein synthesis and improve extensibility. Objective: To compare the use of therapeutic thermal and non thermal ultrasound, associated with stretching, in the remobilization of the soleus muscle of rats subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
0
0
1
Order By: Relevance
“…Two weeks of immobilization can cause loss of myofibrils and decrease of the size of muscle fibers (Ploug et al, 1995), changes in the morphology of the fibers and muscle mechanics . Skeletal muscles can be affected by external influences, such as therapeutic immobilization, which changes their biochemical and structural characteristics (Artifon et al, 2012). In a previous study on energy metabolism in muscle atrophy (Stein & Wade, 2005) results showed an increase in enzyme expression values related to gluconeogenesis in the liver, indicating a higher consumption of liver glycogen, which supports the data obtained in this study, considering that a decrease in liver glycogen in immobilized animals was also observed.…”
Section: Discussionsupporting
confidence: 88%
“…Two weeks of immobilization can cause loss of myofibrils and decrease of the size of muscle fibers (Ploug et al, 1995), changes in the morphology of the fibers and muscle mechanics . Skeletal muscles can be affected by external influences, such as therapeutic immobilization, which changes their biochemical and structural characteristics (Artifon et al, 2012). In a previous study on energy metabolism in muscle atrophy (Stein & Wade, 2005) results showed an increase in enzyme expression values related to gluconeogenesis in the liver, indicating a higher consumption of liver glycogen, which supports the data obtained in this study, considering that a decrease in liver glycogen in immobilized animals was also observed.…”
Section: Discussionsupporting
confidence: 88%
“…-Não houve alteração na expressão de mRNA de MyoD no grupo US em relação aos demais grupos para nenhum período de tempo analisado. Artifon, et al, 2012 Imobilização em flexão plantar máxima do membro posterior direito de ratos por 15 dias. 4 grupos de 7 animais: grupo -Alongamento: Flexão dorsal máxima manual do tornozelo até o limite de tensão tecidual em 3 séries de 30 s por 10 dias;…”
Section: Rocha 2010unclassified